Peran Lembaga Masyarakat dalam Pencegahan Tawuran Remaja di Wilayah RW 07 Kelurahan Galur Kota Administrasi Jakarta Pusat - Muhammad Hanif Ikhsan; Almisar Hamid (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This study aims to find out the role of community institutions in the prevention of brawl violence in the RW 07 area of Galur Village, Central Jakarta. The data collection techniques used in this study are observation, interviews and documentation. The resource persons in this study amounted to 6 people, namely the Chairman of RW 07, LMK RW 07, Chairman of RT 04 RW 07, RW 07 Youth Organization, Religious Leaders and Hansip. The results of the study show that community institutions have an important role in preventing adolescent brawls, especially through social, cultural, and religious activities that aim to build discipline, togetherness, and a sense of responsibility among adolescents. In addition, the active involvement of community leaders and security forces also contributes to creating a conducive environment to prevent conflicts between youth groups. Therefore, closer cooperation is needed between community institutions, the government, and other interested parties to optimize efforts to prevent adolescent brawls in this region. With the effective role of community institutions, it is hoped that a safe and conducive environment can be created, and adolescents can grow and develop in a positive situation.